O impacto da produção antecipada de provas para a obtenção da duração razoável do processo - Cruz, Isabela Raposo (2021)
The present study aims to investigate how the Anticipated Production of Evidence, as introduced in the Brazilian legal system by articles 381 et seq. of CPC/15, impacts on obtaining a reasonable duration of the process. Initially, the relationship between the CPC/15 and the fundamental norms of the Federal Constitution is verified, with emphasis on the principles extolled by the CPC/15 in its inaugural articles. Thus, a study is carried out on the principle of reasonable duration of the process, the historical context of its introduction in the Brazilian legal system until its incorporation into the Federal Constitution, as well as the challenge faced by law practitioners in its practical application. Subsequently, an in-depth study of the Anticipated Production of Evidence is carried out, with the analysis of its historical development, modalities and hypotheses of fit before and after the advent of CPC/15, as well as similar institutes verified in common law countries, such as English disclosure and North American discovery. Finally, given the results obtained, it is concluded that the Anticipated Production of Evidence positively impacts the achievement of a reasonable duration of the process, especially in relation to the following aspects: (i) relieving the Judicial System, by promoting agreements and adoption of alternative dispute resolution methods, as well as providing the parties with a better understanding of their effective position in any future action; (ii) celerity verified in the processing of the Anticipated Production of Evidence; and (iii) celerity provided for any future action in which the material right underlying the dispute will be discussed, through the possibility of using the pre-constituted evidence